The severity of NAFLD is associated with the risk of urolithiasis. Issue 2 (3rd April 2019) - Qin, S; Wang, J; Zhou, C; Zhang, Y; Xu, Y; Wang, X; Wang, S
ABSTRACT: Background and aims : Population-based studies suggest a strong association between the presence of nonalcoholic fatty liver disease (NAFLD) and an increased risk of urolithiasis. However, the available information on the association of the severity of NAFLD with urolithiasis is limited. We hypothesised a link between the severity of NAFLD and the risk of urolithiasis. Methods : We recruited 1527 adult patients with NAFLD who completed a comprehensive health checkup. The severity of NAFLD was measured with AST to platelet ratio (APRI score). Logistic regression analysis was used to detect the association of APRI score with the risk of urolithiasis among NAFLD patients. ROC analysis was used to assess the diagnostic value of APRI score for identifying urolithiasis among NAFLD patients. Results : Multivariate analysis showed three independent risk factors for urolithiasis: obesity (OR 2.06 95%CI 1.35–3.13), APRI score (OR 1.29 95%CI 1.05–1.59), and serum uric acid (OR 1.07 95%CI 1.05–1.09), suggesting an independent association between the noninvasive staging of liver fibrosis and the risk of urolithiasis in NAFLD patients. A three-variable model (obesity, APRI score, and serum uric acid) with an AUROC of 0.73 (95% CI 0.70–0.75) was significant in identifying urolithiasis. Conclusions : The severity of NAFLD is associated with the risk of urolithiasis among NAFLD patients. Moreover, a three-variable model (obesity, APRI score, serum uric acid) could serve as a useful tool for identifying individuals at high risk for urolithiasis in these patients.